Problem of structuring the state organs regulation operation and maintenance of aviation - Кордянін, Ю. І. (Proceedings of National Aviation University (archive), 1998)
Considered are the factors which produce negative influence in safety of flights, also the main elements of functioning of the state system sustaining airworthinees of airplanes and their function as to technical maintenance. It is recommended to joint the functions, connected with technical maintenance and operation under one operative management while forming the structure and personnel on the staff of aviation administration of the countries with limited financial and personnel resources